Qualitative and quantitative impacts assessment of contagious bovine pleuropneumonia in Fulani pastoral herds of North-central Nigeria: the associated socio-cultural factors (2016)
Contagious bovine pleuropneumonia is one of the most important trans-boundary disease affecting Fulani cattle herds of Nigeria and whose control is urgently needed. A Participatory Epidemiology approach and cross-sectional study were concurrently conducted to investigate qualitative and quantitative impacts of CBPP, respectively and associated socio-cultural factors that influenced exposure of Fulani nomadic pastoral communities to its risk in Niger State, North-central Nigeria between January and December 2013.A total of nine pastoral communities were purposively selected for qualitative impact assessment using Participatory Rural Appraisal tools, while 765 cattle randomly sampled from 125 purposively selected nomadic herds were analyzed using c-ELISA. Data on socio-cultural characteristics were collected using structured questionnaires administered on nomadic herd owners of the 125 selected herds. Kendall’s Coefficient of Concordance W statistics and Open Epi 2.3 were used for statistical analyses. Pastoralists’ dependent factors associated with their socio-cultural activities were tested using Chisquare tests and likelihood backward logistic regressions. The mean proportional piles (relative qualitative impact) of CBPP was 12.6%, and nomads agreement on this impact was strong (W = 0.6855) and statistically significant (P < 0.001). This was validated by 16.2% (95% CI: 13.7, 19.0) sero-positive (quantitative impact). Highest sero-prevalence of 25.3% was observed in Northern agro-ecological zone, while lowest of 6.2% was in Eastern zone. Pastoralists in the age groups 51–60 and 61–70 years were more likely (OR 13.07; 95% CI:3.21, 53.12 and OR 7.10; 95% CI: 1.77, 28.33, respectively) to have satisfactory information/awareness on CBPP and lowland transhumance pastoralists were more likely (OR 5.21; 95% CI: 2.01, 13.54) to have satisfactory information. Socio-cultural activities of extensive husbandry system was six times more likely (OR 5.79; 95% CI: 2.55, 13.13) to be satisfactory practice that influenced CBPP occurrence in herds, while culture of borrowing and loaning of cattle was twenty times more likely (OR 19.94; 95% CI: 6.36,62.48) to be satisfactory practice that influenced CBPP occurrence in herds. Also, sharing a water source that caused concentration of stocks in one point was fifty three times more likely (OR 53.08; 95% CI:14.91, 189.00) to be satisfactory practice that influenced occurrence of the disease in herds. This study highlighted the critical gap that exists in terms of significant influence of socio-cultural factors on CBPP occurrence in pastoral herds in Nigeria. Thus, CBPP surveillance, control and prevention programs that take these factors into consideration will be beneficial to the livestock industry in Nigeria, and indeed Africa.